Kajian tentang Ibadah Online Bagi Kaum Lansia di Masa New Normal Pandemi Covid-19 - Livia Danita; Maria Evvy Yanti (KHARISMATA: Jurnal Teologi Pantekosta, 2022)
This paper was written to review the implementation of Online Worship for the elderly in the new normal period in connection with the COVID-19 pandemic which has occurred since December 2019 and has not subsided until November 2021. Government regulations through the new normal protocol have limited social gatherings, including church services, to break the chain of spreading this deadly COVID-19 virus. At this time, the holding of onsite services/church buildings has been allowed as long as it is enforced by complying with strict health protocols, however, the elderly are a group of people who are considered to have high vulnerability or risk and are prohibited from attending worship in the church building. Yet church attendance is one of the foundations of spiritual life associated with worship and fellowship. Therefore, the churches have taken the initiative to hold online services based on the internet, to carry out services in the homes of each congregation. For the elderly, this is something new and becomes a problem in itself because of the need for technological mastery in participating in online worship. This writing is a literature study to review the implementation of online worship for the elderly, whether online worship can fulfill the worship and fellowship of the elderly, and how the church can maximize its services during this pandemic, especially for the elderly. AbstrakPaper ini ditulis untuk meninjau penyelenggaraan Ibadah Online bagi kaum lansia (lanjut usia) di masa new normal sehubungan dengan pandemi COVID-19 yang telah terjadi sejak bulan Desember 2019 dan masih belum mereda sampai bulan November 2021 ini.  Peraturan pemerintah melalui protokol new normal telah membatasi pertemuan sosial, termasuk ibadah di gereja, demi memutus rantai penyebaran virus COVID-19 yang mematikan ini.  Pada saat ini, penyelenggaraan ibadah onsite/gedung gereja telah diperbolehkan sepanjang diberlakukan dengan mematuhi protokol kesehatan yang ketat, namun demikian kaum lansia merupakan golongan kelompok masyarakat yang dipandang memiliki kerentanan atau resiko tinggi dilarang mengikuti ibadah di gedung gereja. Padahal kehadiran di gereja adalah salah satu dasar kehidupan spiritual yang terkait dengan penyembahan, dan persekutuan.  Oleh karena itu gereja-gereja telah berinisiatif untuk mengadakan ibadah secara online yang berbasis internet, untuk melaksanakan ibadah di rumah masing-masing jemaat. Bagi kaum lansia hal ini merupakan hal baru dan menjadi kesulitan tersendiri karena diperlukannya penguasaan teknologi dalam mengikuti ibadah online. Penulisan ini merupakan studi kepustakaan untuk meninjau penyelenggaraan dari Ibadah online bagi lansia, apakah ibadah online dapat memenuhi penyembahan dan persekutuan dari bagi kaum lansia dan bagaimana gereja dapat memaksimalkan pelayanannya pada masa pandemi ini terutama bagi kaum lansia.